Transesterification of palm oil using free and immobilized lipase from pseudomonas species for biodiesel production - Jafri, Nida (2013)
Refined palm oil (RPO) was used as the feedstock for the synthesis of fatty acid methyl ester (FAME) commonly called as biodiesel by transesterification process. The proximate fatty acid composition of RPO used showed it contained high amount of oleic acid and palmitic acid at 54% and 33%, respectively indicating a good potential of raw feedstock for biodiesel production. The transesterification reaction was done using a mixture containing RPO and methanol in n-hexane as a medium with lipase as catalyst in a batch STR. The scouting of lipase was conducted in the same set-up with lipase from Pseudomonas species (PS) and Penicillium camembertii (PC). The scouting result showed efficient conversion of FAME by lipase PS as compared to lipase PC. Therefore all the subsequent work used lipase PS. Effects of molar ratio of RPO to alcohol, molar concentration of RPO, amount of lipase dosage and reaction time on the composition of biodiesel were investigated. The optimum conditions obtained were as follows: methanol to RPO molar ratio- 3:1, RPO concentration- 0.9 M, enzyme dosage- 50 units/mg at reaction temperature- 40oC after 72 hours. The composition of FAME was determined by gas chromatography-mass spectrometry (GC-MS) and results showed a total FAME yield of 92%. An eco-friendly immobilized lipase was also designed by entrapment technique in calcium alginate beads in an attempt to further improve the yield of biodiesel and reusability of lipase. Transesterification was performed using the same optimized reaction conditions as in the free lipase experiment. The experimental result showed a maximum biodiesel yield of 97% in STR which was higher than the yield given by free lipase PS in STR at 92%. The reusability and stability of immobilized lipase was tested for consecutive transesterification experiment. A yield of 77% was obtained after the fourth batch cycle. There was no physical deformation in the structure of the beads which indicated a high mechanical stability of the beads even after four batch cycles under continuous mixing at 150 rpm. A preparatory scale-up of transesterification reaction was also done in an oscillatory flow reactor (OFR) using free and immobilized lipase PS. The main purpose of using OFR was to improve mixing condition with higher reaction volume and shortening overall reaction time. The reaction was conducted with 2.5 kg of RPO at molar ratio of 3:1 in n-hexane medium. Maximum conversion of 98% and 97% was obtained after a reaction time of 2 hrs from free-suspended lipase and immobilized lipase, respectively. This study showed lipase PS exhibited excellent catalyst quality for FAME production and a further improvement in productivity when immobilized lipase was used. There was a 37 fold of improvement in FAME productivity when using OFR as compared to STR. The OFR also reduced the reaction time and gave a good biodiesel yield. Results from this study showed a positive indication for the potential use of OFR in industry for biodiesel production.